Chitosan-based polymer hybrids for thermo-responsive nanogel delivery of curcumin. (1st February 2018) - Luckanagul, Jittima Amie; Pitakchatwong, Chutamart; Ratnatilaka Na Bhuket, Pahweenvaj; Muangnoi, Chawanphat; Rojsitthisak, Pranee; Chirachanchai, Suwabun; Wang, Qian; Rojsitthisak, Pornchai
Highlights: Chitosan-grafted pNIPAM copolymers with the thermo-responsive behavior were synthesized. Degree of pNIPAM substitution on chitosan backbone affects the physical properties of the prepared polymers. Drug loading efficiency of the nanogel formulations depends on the degree of pNIPAM substitution. The nanogel formulations (with and without curcumin) are relatively safe. CS-g-pN nanogels can deliver curcumin into tested cells and showed the dose-dependent cytotoxicity against cancer cells. Abstract: The purpose of this study is to design and develop thermoresponsive nano-sized hydrogel particles from a natural polymer, chitosan, as smart material platforms for curcumin delivery. Chitosan was used as the backbone material to be grafted with poly–(N-isopropylacrylamide) (pNIPAM) using an EDC/NHS coupling reaction. The conjugated products were characterized by 1 H NMR and TGA. Chitosan-grafted pNIPAM (CS-g-pN) nanogels were prepared by a sonication method. The loading of curcumin into the CS-g-pN nanogels was achieved using an incubation method. Size, morphology of nanogels, amounts of curcumin loaded to the nanogels and cellular uptake were investigated by DLS, TEM, fluorescent spectroscopy and confocal microscopy techniques, respectively. A CellTiter-Blue ® cell viability assay was performed in NIH-3T3 and HeLa cells to assess the safety while MTT assay was carried out in MDA-231, Caco-2, HepG2, and HT-29 cells for determining cytotoxic effects. Results showed that CS-g-pN with 3–60% degree of modification were simply assembled into spherical nanogel particles with submicron sizes, in which curcumin was encapsulated. The thermoresponsive behavior of each CS-g-pN nanogel formulation differed due to the grafted pNIPAM length and density. The CS-g-pN nanogel formulations were non-toxic towards NIH-3T3 and HeLa cells. Each curcumin-loaded CS-g-pN nanogel formulation could be up taken into NIH-3T3 cell lines and showed the dose-dependent cytotoxicity against tested cell lines. Successful development of this curcumin-loaded nanogel will lead to advanced materials that can be functionalized and optimized for targeted therapy and controlled delivery of small molecules and/or biomolecules for biomedical applications.